The seroprevalence of West Nile Virus in Israel: A nationwide cross sectional study. - Ravit Bassal; Tamy Shohat; Zalman Kaufman; Batya Mannasse; Eilat Shinar; Doron Amichay; Mira Barak; Anat Ben-Dor; Adina Bar Haim; Daniel Cohen; Ella Mendelson; Yaniv Lustig (PLoS ONE)
West Nile Virus (WNV) is endemic in Israel, affecting yearly 40-160 individuals. Israel is located on a central migratory path between Africa and Eurasia and most West Nile Fever (WNF) cases reported in recent years were among residents of the coastal plain. The aim of the study was to evaluate the seroprevalence of WNV among the Israeli population and to assess correlates for WNV infection. A cross-sectional nationwide serologic survey was conducted using 3,145 serum samples collected by the national Israeli serum bank during 2011-2014, representing all age and population groups in Israel. Prevalence rates of WNV IgG antibodies were determined. Logistic regressions models were applied to assess the associations between demographic characteristics and WNV seropositivity. 350 samples were positive to WNV (11.1%; 95%CI: 10.0-12.3%). In the multivariable analysis, there was a significant association between seropositivity and the Arab population group vs. Jews and others (OR = 1.86, 95%CI: 1.37-2.52), the time lived in Israel [50-59 years vs. 0-9 years; OR = 10.80 (95%CI: 1.03-113.46) and ≥60 years vs. 0-9 years; OR = 14.00 (1.32-148.31)] residence area] Coastal Plain, Inland Plain (Shfela) and Great Rift Valley vs. Upper Galilee; OR = 2.24 (95%CI: 1.37-3.65), OR = 2.18 (95%CI: 1.18-4.03), OR = 1.90 (95%CI: 1.10-3.30), respectively [and rural vs. urban settlement (OR = 1.65, 95%CI: 1.26-2.16). People, who reside in the Coastal Plain, Inland Plain and Great Rift Valley, should be aware of the risk of contracting WNV and reduce exposure to mosquito bites, using insect repellents, and wearing protective clothing. The Ministry of Environmental Protection should be active in reducing the mosquito population by eliminating sources of standing water, a breeding ground for mosquitoes.